PENGARUH PDRB DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI SULAWESI TENGGARA - Alce Syahfrida Pratiwi; Nur Asizah Asizah; Ilyas Ilyas (Universitas Halu Oleo, 2021)
This study aims to determine the influence of Gross Regional Domestic Product (GDP) and Human Development Index (HDI) on Poverty in Southeast Sulawesi period 2005-2019. The data used in this study are GDP data on the basis of constant price, human development index (HDI), as well as poverty data with secondary data types that are quantitative time series. The analysis tool used is multiple linear regression analysis using SPSS. The results of the analysis showed that partially GDP has a negative and significant influence on Poverty in Southeast Sulawesi, and the Human Development Index (HDI) has a negative and significant influence on Poverty in Southeast Sulawesi while collectively / simultaneously GDP and Human Development Index (HDI) has a positive and significant effect on Poverty in Southeast Sulawesi.